T Cell Protein Tyrosine Phosphatase in Glucose Metabolism - Wang, Ya-nan; Liu, Shiyue; Jia, Tingting; Feng, Yao; Xu, Xin; Zhang, Dongjiao (Frontiers in Cell and Developmental Biology, 2021)
T cell protein tyrosine phosphatase (TCPTP), a vital regulator in glucose metabolism, inflammatory responses, and tumor processes, is increasingly considered a promising target for disease treatments and illness control. This review discusses the structure, substrates and main biological functions of TCPTP, as well as its regulatory effect in glucose metabolism, as an attempt to be referenced for formulating treatment strategies of metabolic disorders. Given the complicated regulation functions in different tissues and organs of TCPTP, the development of drugs inhibiting TCPTP with a higher specificity and a better biocompatibility is recognized as a promising therapeutic strategy for diabetes or obesity. Besides, treatments targeting TCPTP in a specific tissue or organ are suggested to be considerably promising.